A CASE OF OSTEOMALACIA SHOWING THE CHARACTERISTICS OF SPONDYLOARTHROPATHY - Güldal Funda Nakipoğlu; Ayşe Karamercan; Aynur Karagöz; Neşe Özgirgin (Archives of Rheumatology, 2003)
Osteomalacia is a metabolic bone disease that results from defective bone mineralization and may present with a variety of clinical and radiographic manifestations mimicking other musculoskeletal disorders. In this article a case of osteomalacia showing the characteristics of spondyloarthropaty was presented.